NATIONAL APPROACHES TO THE NORMALIZATION OF WATER USE AT ENTERPRISES OF THE REPUBLIC OF BELARUS AND THE WAYS OF THEIR IMPROVEMENT - Polina N. Zakharko; Sniazhana A. Dubianok (Водное хозяйство России: проблемы, технологии, управление)
The article discusses methodological approaches to the development of norms, standards for water consumption and wastewater disposal, aimed at the rational use of water resources, as well as substantiates the need to develop a document that establishes the criteria and procedure for assessing the effectiveness of water protection activities in the use and protection of water resources for any enterprise in the Republic of Belarus. The directions for improving the legislation of the Republic of Belarus in terms of regulation of water use are proposed, taking into account the experience of the Russian Federation.